Microbial Bioremediation of Petroleum-Contaminated Soil: A Sustainable Approach - Nordin, Ahmad Rizal Roslan; Navarro, Ariela Rose; Reyes, Juan Carlos; Maragathavalli, S.; Kristanti, Risky Ayu; Wulandari, Retno; Bunrith, Seng (Tropical Aquatic and Soil Pollution, 2025)
Petroleum-contaminated soil is a significant environmental concern caused by oil spills, leakage from storage tanks, industrial discharges, and improper disposal of petroleum products during extraction, refining, and transportation processes. Globally, approximately 6 million tonnes of petroleum are released into the environment each year, leading to soil contamination that poses toxic risks to groundwater, ecosystems, plant life, and human health. The primary aim of this paper is to evaluate the effectiveness and potential of microbial bioremediation for treating petroleum-contaminated soils, offering a sustainable alternative to conventional methods. Traditional remediation approaches such as soil excavation, washing, chemical oxidation, and incineration are often expensive and environmentally disruptive. In contrast, bioremediation using microbes is cost-effective, sustainable, and environmentally friendly. Several microbial strategies are discussed, including natural attenuation, bioaugmentation, and biostimulation. Natural attenuation relies on indigenous microbes, whereas bioaugmentation involves adding hydrocarbon-degrading microbes, and biostimulation enhances microbial activity by supplying nutrients. Among these, bioaugmentation and biostimulation are generally more effective than natural attenuation in degrading petroleum hydrocarbons. However, microbial bioremediation faces challenges such as long treatment durations, incomplete degradation with free microbes, and the need for site-specific optimal conditions. Future research should focus on enhancing microbial efficacy through genetic engineering or microbial consortia, developing faster, site-specific solutions, assessing long-term ecological impacts, and integrating bioremediation with other green technologies. Overall, microbial bioremediation presents a promising strategy for the sustainable management of petroleum-contaminated soils due to its low cost, minimal environmental impact, and adaptability. Key topics addressed include the environmental impact of petroleum pollution, conventional and biological remediation techniques, comparative effectiveness, and future development needs. The relevant keywords are: bioremediation, petroleum hydrocarbons, bioaugmentation, soil contamination, and microbial degradation.